Lymphohaematopoietic system cancer incidence in an urban area near a coke oven plant: an ecological investigation. Issue 3 (1st March 2003) - Parodi, S; Vercelli, M; Stella, A; Stagnaro, E; Valerio, F
Abstract : Aims: To evaluate the incidence risk of lymphohaematopoietic cancers for the 1986–94 period in Cornigliano, a district of Genoa (Italy), where a coke oven is located a few hundred metres from the residential area. Methods: The whole of Genoa and one of its 25 districts (Rivarolo) were selected as controls. The trend of risk around the coke oven was evaluated via Stone's method, while the geographic pattern of such risks across the Cornigliano district was evaluated by computing full Bayes estimates of standardised incidence ratio (FBE-SIR). Results: In males, elevated relative risks (RR) were observed for all lymphohaematopoietic cancers (RR 1.7 v Rivarolo and 1.6 v Genoa), for NHL (RR 2.4 v Rivarolo and 1.7 v Genoa), and for leukaemia (RR 2.4 v Rivarolo and 1.9 v Genoa). In females, statistically non-significant RR were observed. In males no excess of risk was found close to the coke oven. In females, a rising risk for NHL was observed approaching the plant, although statistical significance was not reached, while the risk for leukaemia was not evaluable due to the small number of cases. Analysis of the geographic pattern of risk suggested the presence of a cluster of NHL in both sexes in the eastern part of the district, where a foundry had been operational until the early 1980s. A cluster of leukaemia cases was observed in males in a northern part of the area, where no major sources of benzene seemed to be present. Conclusions: The estimated risks seem to be slightly or not at all related to the distance from the coke oven. The statistically significant higher risks observed in males for NHL and leukaemia, and the clusters of leukaemia in males and of NHL in both sexes deserve further investigations in order to trace the exposures associated with such risks.